Cooperation, Competition, and Specialized Metabolism in a Simplified Root Nodule Microbiome - Bridget L. Hansen (American Society for Microbiology, 2020)
ABSTRACT Microbiomes associated with various plant structures often contain members with the potential to make specialized metabolites, e.g., molecules with antibacterial, antifungal, or siderophore activities. However, when and where microbes associated with plants produce specialized metabolites, and the potential role of these molecules in mediating intramicrobiome interactions, is not well understood. Root nodules of legume plants are organs devoted to hosting symbiotic bacteria that fix atmospheric nitrogen and have recently been shown to harbor a relatively simple accessory microbiome containing members with the ability to produce specialized metabolites in vitro. On the basis of these observations, we sought to develop a model nodule microbiome system for evaluating specialized microbial metabolism in planta. Starting with an inoculum derived from field-grown Medicago sativa nodules, serial passaging through gnotobiotic nodules yielded a simplified accessory community composed of four members: Brevibacillus brevis, Paenibacillus sp., Pantoea agglomerans, and Pseudomonas sp. Some members of this community exhibited clear cooperation in planta, while others were antagonistic and capable of disrupting cooperation between other partners. Using matrix-assisted laser desorption ionization–imaging mass spectrometry, we found that metabolites associated with individual taxa had unique distributions, indicating that some members of the nodule community were spatially segregated. Finally, we identified two families of molecules produced by B. brevis in planta as the antibacterial tyrocidines and a novel set of gramicidin-type molecules, which we term the britacidins. Collectively, these results indicate that in addition to nitrogen fixation, legume root nodules are likely also sites of active antimicrobial production.